SIMULATION OF TURBULENT FLOW IN A TWO-STROKE GRAIL ENGINE CYLINDER - Syed, Shoeb Ahmed; Oyekola, Peter (Journal of Applied Engineering Science, 2022)
This paper investigates the implementation of computational fluid dynamics for the analysis of a grail internal combustion engine. This is intended to analyse the intake hole and channel shape variables as well as their corresponding influence on the fluid flow properties within the cylinder. Due to the geometry of the engine design which features an intake valve positioned directly on the piston, the combustion efficiency is therefore heavily dependent on the flow characteristics. This necessitates the need to understand and analyse the effects of intake hole and duct geometry as well as piston motion on flow dynamics. A numerical simulation using Autodesk CFD finite element solver was used to simulate the engine flow dynamics of the Grail engine. The results of the analysis show a violent tornado-like effect in the flow field as well as an observable swirl effect characterized by a cylinder-centred single vortex. The resultant flow field obtainable from the design of the Grain engines will therefore allow an ideal homogeneous/stoichiometric fuel-air mixture for increased combustion efficiency. The result of both 3-D static and dynamic simulations of the flow through the engine provided guidelines on the selection of several geometrical parameters for optimal performance. The pressure inside the cylinder of the Grail Engine is validated with the experimental setup. The values of TKE obtained from the numerical simulation are well within the limits obtained from the references.
Keywords: grail engine, two-stroke engine, autodesk CFD simulation